Design of a sub 100-femtosecond X-ray streak camera - Li, B; Rajeev, P; Gregori, G; Benetou, M; Dobson, B; Cavalleri, A; Pickworth, L; Lau, P; Jaanimagi, P; Read, F; Lynn, J; Neely, D (2009)
The temporal resolution of existing streak cameras are limited by electron transit time dispersion. Here we present a state-of-art design compensating this to achieve a breakthrough of 100fs time resolution. © 2009 Optical Society of America.